CONSTITUTIONAL REFORM AND BREXIT - Wilson, Gary. ([S.l.])
1 online resource
Keywords: This book examines the extent to which Brexit has impacted upon the operation of the British Constitution, prompting in turn consideration of how some of the factors which contributed to the outcome of the 2016 referendum, as well as the event of Brexit itself, might inform debates surrounding constitutional reform moving forward. The work seeks to make sense of the constitutional implications of Brexit and to revisit some of the key debates that have taken place in respect of particular constitutional reform proposals in order to assess the extent to which recent Brexit-related developments inform the perspectives which are taken upon their merits and prospects. The book is divided into two parts. The first provides some context for the substantive treatment of the potential impact of Brexit on constitutional reform debates which forms the focus of Part II. Part II centres on various specific constitutional reform themes or issues, which are explored further within the context of Brexit. For each such issue, the main parameters of the debates which have taken place are sketched out before moving on to consider how it has informed, or may come to be informed, by the phenomenon of Brexit. By so doing, it looks to some future directions for constitutional reform which take account of the factors driving the discourses which gave rise to the referendum outcome and subsequent developments, as well as offering meaningful responses to these. The book will be of interest to academics, researchers and policy-makers working in the areas of constitutional law, constitutional politics, philosophy and history.